2008
DOI: 10.3354/meps07502
|View full text |Cite
|
Sign up to set email alerts
|

Annual reproductive rates of Weddell seals in eastern Antarctica from 1973 to 2000

Abstract: This study is based on mark and re-sight observations of Weddell seals Leptonychotes weddelli at the Vestfold Hills (68°S, 78°E), which form a considerable time series (1973 to 2000) pertaining to Prydz Bay in eastern Antarctica. We use multi-strata modeling to estimate annual rates of reproduction and survival whilst taking into account annual and breeding state-specific re-sight probability. Inter-annual variation in both the proportion of females producing pups and the proportion of pups surviving juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…Accordingly, the vital rate estimates reported here provide useful baselines that can be compared with what is found under contrasting circumstances for Weddell seals or other closely related species in the Southern Ocean. Estimates of adult survival rates and breeding probabilities for Weddell seals in eastern Antarctica are available for 26 recent years (Lake et al 2008). Similar to what we report here, Lake et al (2008) found that breeding females had consistently high annual survival rates but variable breeding probabilities and used a flexible breeding strategy to avoid reproductive costs to survival.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Accordingly, the vital rate estimates reported here provide useful baselines that can be compared with what is found under contrasting circumstances for Weddell seals or other closely related species in the Southern Ocean. Estimates of adult survival rates and breeding probabilities for Weddell seals in eastern Antarctica are available for 26 recent years (Lake et al 2008). Similar to what we report here, Lake et al (2008) found that breeding females had consistently high annual survival rates but variable breeding probabilities and used a flexible breeding strategy to avoid reproductive costs to survival.…”
Section: Discussionsupporting
confidence: 82%
“…Estimates of adult survival rates and breeding probabilities for Weddell seals in eastern Antarctica are available for 26 recent years (Lake et al 2008). Similar to what we report here, Lake et al (2008) found that breeding females had consistently high annual survival rates but variable breeding probabilities and used a flexible breeding strategy to avoid reproductive costs to survival. Results from studies of other pinnipeds in the Southern Ocean indicate that there might be some interspecific consistency in this pattern.…”
Section: Discussionsupporting
confidence: 82%
“…We also previously reported a positive association between age at first reproduction and longevity (Hamel et al 2009b). Similar to our results, most studies of large mammals found that reproduction did not affect female survival , Packer et al 1998, Testa 2004, Beauplet et al 2006, Lake et al 2008, Weladji et al 2008. Survival costs of reproduction, however, have been reported in two ungulate populations (Tavecchia et al 2005, Moyes et al 2006 and are also occasionally reported in other long-lived species (Boyd et al 1995, Golet et al 1998), but we currently do not have an explanation for these differences.…”
Section: Probability Of Female Survivalsupporting
confidence: 83%
“…Many Antarctic true seal populations have relatively recent population estimates and are thought to have healthy populations, but they lack longer time series or historical estimates due to the inaccessibility of their remote breeding habitats until recently [24]. Abundance monitoring of Antarctic species may become more important for assessing and managing the effects of climate change and expanding Antarctic fisheries [64], [65], [66].…”
Section: Discussionmentioning
confidence: 99%